PENGARUH KOPETENSI DAN MOTIVASI KERJA TERHADAP KUALITAS PELAYANAN DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BOGOR - R. Achmad Rachmat Sobari (POLITEKNIK LP3I JAKARTA, 2018)
AbstractEfforts to improve the quality of public services today to be one of the biggest agenda in the orientation of government policy. Various efforts that led to the creation of public service quality improvement in all areas has been carried out. Efforts to improve the quality of service is in addition to starting of system services and development and improving the quality of personnel resources service providers, also started with a focus on service improvement based on the networking of information through the involvement of community participation. Related to the public service in the Department of Population and Civil Registration Bogor City. Influence research purposes to analyze the competence and motivation on the Quality of Care Department of Population and Civil Registration Bogor City. This research uses quantitative research approaches Quantitative Eksplanatory to know how big the Influence of Competency and motivation towards Quality Services business of Population and Civil Registration Bogor City and partial regression. Program data analysis using IBM SPSS (Statistical Package for the Social Sciences) Statistics Version 20. The study population were employees of the Department of Population and Civil Registration Bogor City totaled 62, with slovin formula (5%) and a sample of 30 people. Based on the research results: There is a positive and significant impact Competence and motivation together on the Quality of Care Department of Population and Civil Registration Bogor City. The amount of influence competence and motivation together amounted to 76.4%.Keywords: Competence, Work Motivation, and Quality Services